Facilitating nurses' knowledge of the utilisation of reflexology in adults with chronic diseases to enable informed health education during comprehensive nursing care - Elna Steenkamp; Belinda Scrooby; Christa van der Walt (AOSIS, 2012)
An integrative literature review of identified scientific evidence, published from January 2000 to December 2008, of the utilisation of reflexology as complementary and alternative medicine (CAM) modalities to promote well-being and quality of life in adults with chronic diseases was done to facilitate nurses to give informed health education during comprehensive nursing care to patients with chronic diseases. Selected accessible databases were searched purposefully for research articles (N = 1171). Pre-set inclusion criteria were applied during the study selection process. The methodological study quality was reviewed and appraised with appropriate tools from the Critical Appraisal Skills Programme (CASP) and the American Dietetic Association's (ADA) Evidence analysis manual (n = 21). Evidence extraction, analysis and synthesis of studies (n = 18) were done through the evidence class rating and level of strength as prescribed in the manuals of ADA and CASP. Findings indicate statistically significant reduction in the frequency of seizures in patients with intractable epilepsy, an improvement of sensory and urinary symptoms associated with multiple sclerosis and clinically significant reduction of anxiety and pain in patients with cancer and fibromyalgia syndrome. These findings can be utilised by nurses to inform patients with these chronic diseases about alternative ways of treatment. Opsomming 'n Geïntegreerde literatuur oorsig van ge-identifiseerde wetenskaplike bewyse, gepubliseer vanaf Januarie 2000 tot Desember 2008, was gedoen oor die gebruik van refleksologie as aanvullende en alternatiewe behandelingsmodalitieit om welsyn en lewenskwaliteit te bevorder by volwassenes met kroniese siekte om verpleegkundiges te fasiliteer om ingeligte gesondheidsvoorligting te gee gedurende omvattende verpleegsorg aan pasiente met kroniese siektes. Geselekteerde toeganklike databasisse was doelbewustelik deursoek vir navorsingsartikels (N = 1171). Vooraf bepaalde insluitingskriteria was toegepas tydens die selekteringsproses. Die studie gehalte is nagegaan en beoordeel met toepaslike instrumente van die Critical Appraisal Skills Programme (CASP) en die American Dietetic Association (ADA) se Evidence analysis manual (n = 21). Bewys uitreksel, analisering en sintese van studies (n = 18) was gedoen deur die bewysklas gradering en vlak van bewysterkte soos beskryf in die handleidings van ADA en CASP. Bevindings dui op 'n statisitese beduidenisvolle verlaging in die frekwensie van konvulsies by pasiënte met epilepsie, 'n verbetering van sensoriese en urinêre simptome ge-assosieer met veelvuldige sklerose en 'n kliniese beduidenisvolle afname in angstigheid en pyn by pasiënte met kanker en fibromialgiese sindroom. Hierdie bevindings kan deur verpleegkundiges gebruik word om pasiente met hierdie kroniese siektes in te lig omtrent alternatiewe maniere van behandeling.